Effect of N‐Terminal Acylation on the Activity of Myostatin Inhibitory Peptides. (8th March 2016) - Takayama, Kentaro; Nakamura, Akari; Rentier, Cédric; Mino, Yusaku; Asari, Tomo; Saga, Yusuke; Taguchi, Akihiro; Yakushiji, Fumika; Hayashi, Yoshio
Abstract: Inhibition of myostatin, which negatively regulates skeletal muscle growth, is a promising strategy for the treatment of muscle atrophic disorders, such as muscular dystrophy, cachexia and sarcopenia. Recently, we identified peptide A (H‐WRQNTRYSRIEAIKIQILSKLRL‐NH2 ), the 23‐amino‐acid minimum myostatin inhibitory peptide derived from mouse myostatin prodomain, and highlighted the importance of its N‐terminal tryptophan residue for the effective inhibition. In this study, we synthesized a series of acylated peptide derivatives focused on the tryptophan residue to develop potent myostatin inhibitors. As a result of the investigation, a more potent derivative of peptide A was successfully identified in which the N‐terminal tryptophan residue is replaced with a 2‐naphthyloxyacetyl moiety to give an inhibitory peptide three times (1.19±0.11 μm ) more potent than parent peptide A (3.53±0.25 μm ). This peptide could prove useful as a new starting point for the development of improved inhibitory peptides. Abstract : Body building peptides : We focused on the N‐terminal tryptophan residue of mouse myostatin prodomain‐derived peptide A and explored more favorable N‐terminal structure for potent myostatin inhibition. Consequently, we successfully obtained myostatin inhibitory peptide36 with the IC50 value of 1.19 μm, which was three times more potent than that of original peptide A.